Current Perspectives of Matrix Metalloproteinase 11 (MMP11) as a Diagnostic and Therapeutic Target for Cancer - Shobana, Asokan; Deeksha, Remella V.; Rahman, Syed A. A.; Thangaswamy, Tiviya; Oviya, Revathi Paramasivam; Gopisetty, Gopal (Current Cancer Therapy Reviews, 2024)
Matrix metalloproteinase 11 (MMP11), also known as stromelysin-3, is a member of the matrix metalloproteinases family of proteins that are involved in physiological and pathological extracellular matrix remodelling. MMP11 does not hydrolyse classical MMP substrates, such as laminin and fibronectin, and many of its substrates remain unknown, piquing the interest of researchers. Several studies have reported the role of MMP11 in inducing tumour growth by inhibiting apoptosis and promoting cancer cell migration and invasion. Various reports have shown its potential as a diagnostic and prognostic marker in a majority of cancers. MMP11 also induces an immune response as a tumour-associated antigen, and recent evidence shows the involvement of many microRNAs in targeting MMP11 in cancer, with prospective future applications in cancer immunotherapy and gene silencing. Owing to the importance of MMP11 in both cancer diagnosis and therapy, there is a need for deeper understanding of its mechanism and role in tumour progression. The current review focuses on the role of MMP11 in cell signalling pathways, its expression status in various cancers, and its potential in cancer treatment.
Keywords: cancer immunotherapy